2017
DOI: 10.21009/spektra.022.06
|View full text |Cite
|
Sign up to set email alerts
|

Sifat Mekanik Bahan Komposit Kampas Rem Berbahan Dasar Serbuk Arang Kulit Buah Mahoni

Abstract: AbstrakKulit buah mahoni menjadi salah satu bahan yang belum termanfaatkan secara optimal dalam masyarakat. Jumlah kulit buah mahoni yang melimpah akan menimbulkan permasalahan baru berupa sampah. Tingginya jumlah kulit buah mahoni di lingkungan masyarakat menuntut cara penanganan alternatif yang kreatif dan inovatif menjadi produk berdaya guna. Sebuah upaya yang dilakukan adalah pemanfaatan kulit buah mahoni sebagai bahan komposit organik untuk kampas rem. Pembuatan bahan komposit dilakukan dengan mereduksi k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Brinell hardness test is performed to see the maximum strength level of the composite material in holding the load it receives. Hardness testing is performed by measuring the loads capable of being retained by the surface of the composite material sample (Prabowo, et al, 2017). Figure 6 shows a decrease in Brinell hardness of 82, 17 kg/mm 2 -44.09 kg/mm 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brinell hardness test is performed to see the maximum strength level of the composite material in holding the load it receives. Hardness testing is performed by measuring the loads capable of being retained by the surface of the composite material sample (Prabowo, et al, 2017). Figure 6 shows a decrease in Brinell hardness of 82, 17 kg/mm 2 -44.09 kg/mm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The wear resistance test is performed to estimate the amount of mass of the sample lost during friction. Estimation is done by calculating the mass of the graded sample after friction (Prabowo, et al, 2017). Figure 7 shows significant results with graphic trends experiencing a decrease in wear values on composite materials made.…”
Section: Resultsmentioning
confidence: 99%
“…Uji keke rasan Dari grafik tersebut terlihat grafik uji kekerasan yang dimana spesimen A dengan rasio campuran 40% matriks : 60% penguat memiliki nilai HBN tertinggi yaitu 10kg/mm 2 lalu diurutan kedua spesimen B dengan rasio campuran 50% matriks : 50% penguat dengan nilai 8.8kg/mm 2 serta yang paling lunak diantara tiga spesimen diatas adalah spesimen C rasio campuran 60%Matriks:40%Penguat pada angka 6.1kg/mm 2 Sama dengan yang dilakukan penelitian oleh [10] bahwa variasi persentase komposisi berpengaruh pada karakteristik bahan komposit kampas rem. Nilai kekerasan meningkat seiring dengan bertambahnya komposisi arang tempurung kelapa pada bahan komposit, sedangkan massa keausan menurun.…”
Section: Hasil Pengujian Dan Pembahasanunclassified
“…The research findings elucidated that the composite brake pad composition containing up to 55% teak wood powder and up to 45% polyester yielded the highest maximum strength value. Furthermore, another study conducted by (Prabowo et al, 2017) investigated the mechanical properties of composite brake pad materials using mahogany fruit husk charcoal powder as the main ingredient. The research results indicated that the most suitable composition was found to be 60% mahogany husk charcoal, 15% coconut shell charcoal, and 25% polyester resin, which exhibited hardness and wear mass values close to the Indonesian National Standard (SNI).…”
Section: Introductionmentioning
confidence: 99%